Regularities in the formation of wear-resistant coatings on steel samples when machining them with electrical discharge - Dmytro Marchenko (PC Technology Center, 2021)
This paper considers the technology of electrical discharge machining of steel friction pairs and reports the results of experimental studies. Analysis of the experimental studies has shown that increasing the "anode-cathode" voltage leads to a sharp decrease in the micro-hardness of the surface layer. The study has also made it possible to determine the characteristic dimensions of the structural elements, the height parameters of surface roughness. The elemental composition of the resulting surface of a steel 15KHGN2TA sample differs from the composition of coatings and the surface layers of samples modified by electrical discharge machining involving various electrodes. Under the "anode-cathode" system operation mode, a thin layer of coating with a stable modified structure forms on the surface of the cathode due to dissipative processes. It is shown that the height of surface irregularities on sections after friction is higher than on the surface sections outside the friction flow, which is associated with the formation of a friction transfer film on the samples' surface. It was established that the interaction of friction of steel samples treated by electrical discharge machining forms a thin film on the surface of friction of steel samples, which leads to a change in the relief of surfaces with an increase in the height of the micro-protrusions, as well as the structuring of the transfer film in the direction of sliding. The effect of machining steel surfaces by electrical discharge on the wear resistance of metal-polymer tribosystem was established. The implementation of the devised technology could provide a significant increase in the wear resistance of metal-polymer tribojunctions